ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN REAL ESTATE DAN PROPERTY DI BURSA EFEK INDONESIA (BEI) DAN SINGAPURA (SGX) - Hendra Agus Wibowo; Diyah Pujiati (STIE Perbanas Surabaya, 2011)
Financial ratio analysis is considered important in recent years. This paper raises theproblem by questioning whether the financial ratio analysis can be used to predict thechange in profit in Real Estate and Property Companies registered in the BEI and SGX. It isalso requested whether there are differences in financial ratio analysis to predict changes inprofit in Real Estate and Property companies between BEI and SGX. The purpose of thisstudy to provide empirical evidence concerning the effect of financial ratio analysis forpredicting changes in income and whether there are differences in financial ratio analysis inpredicting changes that affect company profits on real estate and property in BEI and SGX.To test the hypothesis in this study, the research uses Multiple Linear Regression Method andChow Test with a significance level of 0.05. it can be generalized that the current ratio andprofit margin have a significant effect in predicting earnings changes in real estate andproperty companies in BEI. Turnover of total assets and profit margins have a significanteffect in predicting earnings changes in real estate and property companies in SGX. And, thechow test can be concluded that there are differences that affect the financial ratio analysisin predicting earnings changes in real estate and property companies in BEI and SGX